Significance of Transformational Leadership on Project Portfolio Success within the Micro Financial Sector in Cameroon - Ngochembo, Gaston Gwemelang; Ful , Honest Kfetua; Mbouh, Vera Bekebang (Finance & Economics Review, 2024)
Purpose: This research investigates the effect of transformational leadership on project portfolio success in the micro-financial sector in Cameroon. Method: A quantitative research approach was used for this study. Data were collected from 205 managers of Microfinance institutions in Cameroon and analyzed with the help of the SPSS, version 25. AMOS 23 was used to conduct Confirmatory Factor Analyses to examine convergent and discriminant validity. Results: The result showed that less than 60% of current microfinance institutions have adopted key aspects of transformational leadership (idealized influence; intellectual stimulation; inspirational motivation; and individualized consideration). It was observed that transformational leadership has a significant and positive effect on project portfolio success. The effect of such leadership is mediated by team building practices and teamwork quality. Implication: Transformational leadership is not well recognized in the micro-financial sector of Cameroon irrespective of its effect on project portfolio success. Microfinance institution managers should adopt and apply such leadership for higher performance of their project portfolios.